BALALARDÍŃ MEKTEPKE SHEKEMGI BILIMLENDIRIW SHÓLKEMINIŃ TURMÍS TÁRIZINE MASLASÍWÍ (Uzbek Scholar Journal, 2022)
At present, great attention is paid in the Republic of Uzbekistan to ensuring the full coverage of each young child with preschool education. It should be noted that for the first time having crossed the vice of a preschool institution, the child undergoes adaptation from the biological and psychological sides, also, taking into account the possibilities of adaptation of children, mild, moderate and severe degrees are observed. To implement the action of this process, a close relationship between parents and educators is necessary.